TINGKAT KONTROL DIRI REMAJA DALAM MENGGUNAKAN APLIKASI TIKTOK DI KELURAHAN TIMBANGAN - Indah Rahmadhani, Tri; Nurrizalia, Mega; Sri Andriani, Dian (SATUKATA: Jurnal Sains, Teknik, dan Studi Kemasyarakatan, 2023)
This study aims to determine the level of self-control in adolescents in using the TikTok application in Timbangan Village. This type of research is descriptive analysis using a quantitative approach. Data collection techniques were carried out using questionnaires, observation and literature study. The sample of this study amounted to 61 people who were teenagers aged 11-13 years who used the TikTok application in Timbangan Village, the determination of this sample was carried out by calculating the slovin formula and specified by purposive sampling technique. The results show that the level of self-control of adolescents in using the TikTok application in Timbangan Village is 74.19% with a high category of behavior control indicators and control decisions because most adolescents are able to set limits on themselves and make good decisions for themselves in using the TikTok application. In the cognitive control indicator, it is quite high because a small proportion of teenagers who use the TikTok application in Timbangan Village still often make negative comments on TikTok and do not check content that is not yet clear the truth.